Role of Shrimp Chitin in the Ecology of Toxigenic Vibrio cholerae and Cholera Transmission - Sultana, Marzia; Nahar, Shamsun; Naser, M. Niamul; Nair, Gopinath B.; Watanabe, Haruo; Ohnishi, Makoto; Yamamoto, Shouji; Endtz, Hubert; Cravioto, Alejandro; Sack, R. Bradley; Hasan, Nur A.; Sadique, Abdus; et al. (Frontiers in Microbiology, 2012)
Seasonal plankton blooms correlate with occurrence of cholera in Bangladesh, although the mechanism of how dormant Vibrio cholerae, enduring interepidemic period in biofilms and plankton, initiates seasonal cholera is not fully understood. In this study, laboratory microcosms prepared with estuarine Mathbaria water (MW) samples supported active growth of toxigenic V. cholerae O1 up to seven weeks as opposed to six months when microcosms were supplemented with dehydrated shrimp chitin chips (CC) as the single source of nutrient. Bacterial counting and detection of wbe and ctxA genes were done employing culture, Direct Fluorescent Antibody (DFA) assay, and multiplex PCR (M-PCR) methods. In MW microcosm, the aqueous phase became clear as the non-culturable cells settled, whereas the aqueous phase of the MW-CC microcosm became turbid from bacterial growth stimulated by chitin. Bacterial chitin degradation and biofilm formation proceeded from an initial steady state to a gradually declining bacterial culturable count. V. cholerae within the microenvironments of chitin and chitin-associated biofilms remained metabolically active even in a high acidic environment without losing either viability or virulence. It is concluded that the abundance of chitin that occurs during blooms plays an important role in the aquatic life cycle of V. cholerae and, ultimately, in the seasonal transmission of cholera.